NASSDA as a Data-Collaborative Network to Enhance Social Science Research in East Asia - Pei-Shan Liao; Shuai Wang; Hiroshi Ishida; Hearan Koo; Won-ho Park (Data Science Journal)
International organizations that promote data sharing and collaboration among data depositories have emerged globally and regionally. Such international collaboration, however, is few in regions other than Europe and North America. It is also important to share social science data, given the contributions of social science research. Although the advantages of sharing social science data has been recognized, challenges persist, particularly for data repositories focusing on curation and dissemination. In this article, we introduce the establishment of the Network of Asian Social Science Data Archives (NASSDA), a collaborative network among social science data depositories in East Asia. Its member archives include Chinese National Survey Data Archive (CNSDA), Korean Social Science Data Archive (KOSSDA), Survey Research Data Archive (SRDA), and Social Science Japan Data Archive (SSJDA). Each data archive describes its purposes for establishment, data usage and infrastructure, research and promotion activities, and future developments. Since the establishment of NASSDA in 2016, numerous challenges have impeded progress, including differences in infrastructure and systems for survey data loading, financial and personnel situations, national policies, and domestic circumstances. The current focus of NASSDA is to collaborate within these existing constraints by establishing a website and organizing annual meetings. These initiatives serve as a platform for information exchange and idea sharing, aiming to align the future direction with those of other institutions. This fosters a mutual understanding and paves the way for further collaboration.